Analysis of the Application of Animated Video Media on Students' Understanding of Science Learning - Laura Ariesta; Mega Adyna Movitaria (International Journal of Research, 2023)
This research was conducted based on field observations on third grade elementary school students. This study aims to increase students' understanding of science learning in class III SD through the learning method of animated video media. The research method used is a qualitative method by making observations in the field by forming two different groups, displaying two different learning methods. The first method is carried out by presenting an animated video related to the material to be delivered and the second method is carried out in a way that is usually done by the teacher when teaching, and then observations are carried out with interview sessions and documentation. The research results obtained are that many children are interested in the video animation method, they are more focused on looking at the screen and actively respond when there are several questions presented in the animation. While the delivery of material carried out by their teachers is more likely to be boring, silent, and not responding to questions posed by the teacher. Thus it can be concluded that children are more interested in the animated video learning method compared to the method that is often taught by teachers at school.